Stretched and compressed exponentials in the relaxation dynamics of a metallic glass-forming melt - Zhen Wei Wu (Nature Portfolio, 2018)
Glasses show peculiar relaxation dynamics below glass transition temperature, yet a deeper understanding of this phenomenon is still lacking. Wu et al. show the coexistence of stretched and compressed relaxation in a metallic glass system and attribute their origins to different local cluster structures.